Legacies and lifecycles: digitizing oral histories at Rutgers University libraries. Issue 3 (14th August 2017) - White, Krista; Radick, Caryn
Abstract : Purpose: This paper aims to explore two separate legacy oral history digitization projects at one institution and how the project teams approached the different issues and challenges these projects presented. Design/methodology/approach: The approach compares two case studies of how digitization of legacy oral history collections was carried out. The paper discusses these projects utilizing a lifecycle model approach and reveals how archival and digital humanities perspectives drove some of the projects' differences. Findings: The authors find that when working with digitizing legacy oral history collections, each collection will require different approaches and methods of problem solving. In large institutions with multiple repositories, it can be useful for project teams to consult each other to develop best practices. Practical implications: The two case studies presented in this paper can serve as models for other institutions digitizing many oral history collections and serve as a model for communication and collaboration in larger institutions with multiple repositories. Originality/value: This paper compares and contrasts two case studies of digitization projects involving legacy oral history collections in different units of one large institution. Project teams were influenced by different approaches. One project was conducted by archivists and the other led by a digital humanities librarian. Differing professional foci provided different perspectives about collection characteristics and, subsequently, led to different approaches that impacted implementation of the projects.